1999
DOI: 10.1088/0953-4075/32/15/104
|View full text |Cite
|
Sign up to set email alerts
|

Convergent calculations for simultaneous electron-impact ionization-excitation of helium

Abstract: Theoretical results are presented for electron-impact ionization of He(1s2), leaving the ion in the n = 2 excited states. The projectile-target interaction is described in the first-order plane-wave Born approximation, whereas the interaction between the ejected electron and the residual ion is treated non-perturbatively within the convergent close-coupling formalism. Comparison of the predictions from two entirely independent approaches, formulated either in coordinate or in momentum space, provides a basis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
29
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 18 publications
10
29
0
Order By: Relevance
“…Dupré et al [21] reported their ionization-excitation measurement at E 0 Ӎ 5.5 keV and E 2 = 5 , 10, and 75 eV. The first Born results for the two lowest electron energies of 5 and 10 eV are well below the experiment and only for the 75 eV case is agreement with experiment satisfactory [3,4]. The second Born calculations [5,6] are somewhat closer to experiment but significant discrepancies still exist for the two lowest ejected electron energies.…”
Section: A Ionization With Excitationmentioning
confidence: 85%
See 2 more Smart Citations
“…Dupré et al [21] reported their ionization-excitation measurement at E 0 Ӎ 5.5 keV and E 2 = 5 , 10, and 75 eV. The first Born results for the two lowest electron energies of 5 and 10 eV are well below the experiment and only for the 75 eV case is agreement with experiment satisfactory [3,4]. The second Born calculations [5,6] are somewhat closer to experiment but significant discrepancies still exist for the two lowest ejected electron energies.…”
Section: A Ionization With Excitationmentioning
confidence: 85%
“…The first Born term has been investigated in great detail and the benchmark results had been established for the electron-impact ionization excitation of He to the n = 2 state [3,4]. There is also a good agreement between different close-coupling theories for the second Born contribution as far as ionization excitation is concerned [5,6].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown by Kheifets et al [40] for the more complicated simultaneous ionization-excitation process, such expansions make it possible to get effectively converged results for the scattering of the slow ejected electron from the residual He + ion, while still treating the projectile-target interaction perturbatively.…”
Section: Distorted-wave Modelsmentioning
confidence: 99%
“…Even for the coplanar geometry, significant discrepancies between theory and experiment can occur under such conditions, if the part of the projectile-target interaction responsible for ionization is accounted for only to first order [12]. Such experiments were performed by Dupré et al [13] and later by Avaldi et al [14] and Rouvellou et al [15].…”
mentioning
confidence: 99%